The Borzoi handbook for writers - Crews Frederick (McGraw -Hill, 1993)
Designed as an easy-to-use, non-jargon-bound reference for writers, the BORZOI features elegant, straightforward language suggestions and advice as it avoids complex grammatical explanations. The handbook is accompanied by a free Practice book that provides exercises based in real discourse units. --This text refers to the Hardcover edition.